The Importance of Assessing Nutritional Status to Ensure Optimal Recovery during the Chronic Phase of Stroke - Monica C. Serra (Stroke Research and Treatment)
Background. Despite evidence that many of the consequences of stroke that hinder recovery (i.e., obesity, muscle atrophy, and functional declines) have nutritionally modifiable behavior components, little attention has been focused on the significance of nutrition beyond the acute phase of stroke. Objective. This literature review summarizes the evidence for and against the influence of nutrition on optimal recovery and rehabilitation in chronic (>6 months) stroke. Results. The literature, which is mainly limited to cross-sectional studies, suggests that a suboptimal nutritional status, including an excess caloric intake, reduced protein intake, and micronutrient deficiencies, particularly the B-vitamins, vitamin D, and omega 3 fatty acids, may have deleterious effects on metabolic, physical, and psychological functioning in chronic stroke survivors. Conclusions. Careful evaluation of dietary intake, especially among those with eating disabilities and preexisting malnutrition, may aid in the identification of individuals at increased nutritional risk through which early intervention may benefit recovery and rehabilitation and prevent further complications after stroke.